Age and Depositional Environment of the Sandstone Unit of Ciletuh Formation in Ciletuh-Palabuhanratu Geopark - Winantris Winantris; Mega Fatimah Rosana; Katon Sena (Indonesian Journal on Geoscience, 2023)
Sandstones form part of the Cenozoic Ciletuh Formation which is widely exposed in The Ciletuh Palabuhanratu Geopark, Indonesia. This study aims to establish the age of these sandstone units, and to evaluate their depositional environment based on palynological data. Five samples from Ciletuh sandstones were collected for palynomorph analysis. Exposed sections were measured and sampled to determine the stratigraphic position, with palynomorphs being separated from the sediment using acetolysis. Cluster analysis was applied to the resultant palynomorph assemblages and interpreted using plant association model, which refered to the depositional environment of different taxa. Two distinct clusters were identified, characterized by different environmental markers. The first cluster is dominated by Proxapertites operculatus and Proxapertites cursus, while the second cluster is dominated by Podocarpus pollen. While the Proxapertites cluster includes Dicolpopollis kalewensis, Palmaepollenites kutchensis, foraminiferal test linings, dinoflagellates cysts, plant debris, deposited in the marine environment. The Podocarpus cluster consists of Podocarpus pollen, plant debris, foraminiferal test linings, and dinoflagellate cysts, that was deposited in a more distal marine environment. All samples were deposited during the end of Middle Eocene (E6-zone), as defined by the age markers of Proxapertites. cursus, P. operculatus, Restioniidites punctulatus, and Podocarpus pollen.